Применение ионоселективных полевых транзисторов для ферментного анализа токсичных примесей в водных растворах - Pavluchenko, A. S.; Kukla, A. L.; Goltvyanskiy, Yu. V. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The article describes design and production technology of pH-sensors based on ion-selective field-effect transistors (ISFET) intended for enzyme analysis of inhibiting admixtures in aqueous solutions, and architecture of the multichannel measuring system built upon the ISFET-sensors. The characteristics of developed prototypes are given and the ways for further improvement of system design, metrological performance and operating parameters are outlined.